Pharmacokinetics of ciprofloxacin in layer chicks - B. S. AI – Khafaji (University of Baghdad, College of Veterinary Medicine, 1999)
Pharmacokinetics parameters of ciprofloxacin were calculated from constructed plasma disappearing curves (PDC) after oral or i.v. injection of 5mg / kg in two-week old hybird layer · The i.v. PDC indicated a first order biphasic kinetic. The distribution phase was too short to be considered. The parameters of the elimination phase phase indicated that the biological half – life ( t 12) was 3.7 hours and the volume of distribution (Vd) was 1.7 1/kg.